From present to future development pathways in fragile mountain landscapes - Karpouzoglou, Timos; Dewulf, Art; Perez, Katya; Gurung, Praju; Regmi, Santosh; Isaeva, Aiganysh; Foggin, Marc; Bastiaensen, Johan; Hecken, Gert Van; Zulkafli, Zed; Mao, Feng; Clark, Julian; et al. (Elsevier, 2020)
Mountains are dynamic landscapes that are home to rich natural and human heritage. However, climatic variability, globalisation and increasing ecomomic integration are making these landscapes more fragile with implications for present and future development. Using a pathways lens, we examine development trajectories in mountains and relate these to environmental and social-economic change currently taking place. We analyse and compare pathways in three case studies in Peru (Andes); Nepal (Himalayas); and Kyrgyzstan (Tien Shan). The paper highlights that development pathways in fragile mountain regions may be shifting in new directions, but because they emerge out of complex socio-environmental and historical contexts, there are also social risks associated with the articulation of future pathways, particularly in terms of social equity and sustainability. Building on different pathway approaches with their various strengths and weaknesses, this study examines the role of human agency and power, the role of historical and present context and feedbacks between social and ecological features in shaping future development pathways of mountain landscapes.